Mengenal aplikasi figma untuk membuat content menjadi lebih interaktif di era society 5.0 - Maman Suparman; Mita Rosada; M.Lutfi; Putri Kamaliya; Faoziah Sabaniah; Romadhon haris alfian; Fathan ramadhan; Ibra Alfaro; Muhamad Rosdiana (Abdi Jurnal Publikasi, 2023)
Figma is a design tool that is usually used to create mobile, desktop, website and other applications. Figma can be used on Windows, Linux or Mac operating systems by connecting to the internet. Generally, Figma is widely used by someone who works in the field of UI/UX, web design and other similar fields. UI and UX stands for User Interface and User experience, which is a visual display in an application or digital marketing tool in the form of a website that can enhance brand owned by a business or company. In the 5.0 era, the introduction of the figma application in creating interactive content is very necessary because it is very related to this all-digital era. The purpose of this community service is to educate knowledge about the introduction of the FIGMA application which is used in building an interactive user interface and user experience (UX) for students of SMP PGRI PARUNG PANJANG. The method used in this PKM is in the form of seminars or practice. From this dedication it can be concluded that the students participating in the PKM were able to understand the material presented.